Sodium valproate affects the expression of p16INK4a and p21WAFI/Cip1 cyclin‑dependent kinase inhibitors in HeLa cells - Rocha, Marina Amorim; Cardoso, Adauto Lima [UNESP]; Martins, Cesar [UNESP]; Mello, Maria Luiza S. (Spandidos Publications, 2024)
p16INK4a and p21WAF1/Cip1 are cyclin‑dependent kinase inhibitors involved in cell cycle control, which can function as oncogenes or tumor suppressors, depending on the context of various extracellular and intracellular signals, and cell type. In human papillomavirus‑induced cervical cancer, p16INK4a shows oncogenic activity and functions as a diagnostic marker of cervical neoplasia, whereas p21WAF1/Cip1 acts as a tumor suppressor and its downregulation is associated with the progression of malignant transformation. Several histone deacetylase (HDAC) inhibitors promote the positive and nega‑ tive regulation of a number of genes, including p16INK4a and p21WAF1/Cip1; however, the effects of sodium valproate (VPA) on these genes and on the proteins they encode remain uncer‑ tain in HeLa cervical cancer cells. In the present study, these effects were investigated in HeLa cells treated with 0.5 or 2 mM VPA for 24 h, using reverse transcription‑quantitative PCR, confocal microscopy and western blotting. The results revealed a decrease in the mRNA expression levels of p16INK4a and a tendency for p16INK4a protein abundance to decrease in the presence of 2 mM VPA. By contrast, an increase in the protein expression levels of p21WAF1/Cip1 was detected in the presence of 0.5 and 2 mM VPA. Furthermore, VPA was confirmed to inhibit HDAC activity and induce global hyperacetylation of histone H3. Notably, VPA was shown to suppress p16INK4a, a biomarker gene of cervical carcinoma, and to increase the abundance of the tumor suppressor protein p21WAF1/Cip1, thus contributing to the basic knowledge regarding the antitu‑ morigenic potential of VPA. Exploration of epigenetic changes associated with the promoters of p16INK4a and p21WAF1/Cip1, such as histone H3 methylation, may provide further information and improve the understanding of these findings.
Keywords: cyclin‑dependent kinase inhibitors; HeLa cells; p16INK4a; p21WAF1/Cip1; valproate